THE IMPORTANCE OF CUTANEOUS SILENT PERIOD IN UREMIC POLYNEUROPATHY - (:unkn) unknown (NOBEL ILAC, 2011)
Objective: Cutaneous silent period (CSP) is a brief pause in a voluntary contraction following strong stimulation of a cutaneous nerve. Clinical interest in the CS P sterns from its potential usefulness for evaluating segment and components of sensory nerves that are not well assessed by standard electro diagnostic methods. Aim of this study was to determine whether CSP has precedence over standard nerve conduction studies (SNCS) in uremic polyneuropathy Material and Method: The study included 20 chronic hemodialysis patients. Mean age was 42.6 (22-63). Mean uremic period before dialysis and dialysis age were 13.9+7.2 (6-36) and 51.2+46.8 months (12-190), respectively. The eight of patients were symptomatic (paresthesia, pain-burning), the others were asymptomatic. Twenty healthy volunteers were accepted as control group. Standard sensorial and motor nerve conductions and F- responses were recorded in patients. Cutaneous silent period were measured from abductor pollicis brevis (APB) muscle by stimulating third finger and from tibialis anterior muscle by stimulating sural nerve. Results: The significant difference between dialysis and control groups was not found in SNCS. But, at the recording from APB muscle, CSP latency (ms) (82.44+7.80) in hemodialysis patients was longer than controls (63.60+13.70) (p<0.001) and CSP duration (ms) (42.10+9.95) was significantly shorter than controls (51.54+11.24) (p<0.001). At the recording from tibialis anterior muscle, CSP latency (101.90+13.38) was similar with controls (95.03+12.59) (0.1<p<0.5) and CSP duration (34.12+16.09) was significantly shorter than controls (52.95+18.13) (p<0.001). Conclusion: The shortening of CSP duration was thought an antecedent and important method for uremic polyneuropathy as thin fiber neuropathy.
Keywords: Cutaneous silent period; polyneuropathy; uremia; STIMULATION